Collaborative Approach and Scientific Approach in Teaching Writing Descriptive Text - Gymnastiar, Maulana Alif; Apsari, Yanuarti (IKIP Siliwangi, 2019)
This research paper entitled “Collaborative Approach and Scientific Approach in Teaching Writing Descriptive Text”. The objectives of the study was to know wheter or not there was significant different between students who were taught by using Cooperative Script and those who were taught taught by using scientific approach. The method of this research was quantitative method and the design was quasi-experimental design with two groups. The population of this research was eight grade students’ and the sample are VIII A and VIII C. The instruments used in this research were test, observation, and interview. In analyzing the data, the writer used SPSS. The results of this research shows that the Sig of N-Gain test (0,014) was lower than 0,05. It means that Ho of this research was rejected. Thus, the researcher concluded that there were differences between students who were taught by using collaborative approach and those who were taught by using scientific approach.